Systemic Functional Linguistics and Legitimation Code Theory on Education: Rethinking field and knowledge structure - Martin, J. R.; Maton, Karl (Onomázein, 2017)
This paper presents an introduction to how systemic functional linguistics (SFL) and Legitimation Code Theory (LCT) offer complementary insights into education, focusing on key ideas that brought the theories into dialogue over the past decade. It begins with a review of SFL work on field, which foregrounds the role of forms of knowledge in education. It then discusses how SFL scholars engaged with and understood Bernstein’s notions of ‘knowledge structures’ for modelling intellectual fields. This engagement raised a series of questions that were a basis for dialogue with LCT, which extends and integrates Bernstein’s framework. The paper introduces key concepts from two dimensions of LCT —Specialization and Semantics— enacted in papers in this special issue. It then briefly summarizes two major research projects into education that enact these concepts alongside SFL and provide a context to the papers of this special issue, before introducing how these papers illustrate the growing and fruitful transdisciplinary dialogue between SFL and LCT.